Analyzing Student Misconduct in Imaging Sciences Education. - Clark, Jennifer (Radiologic Science & Education, 2024)
This study examined behavioral issues among imaging sciences students in clinical and didactic settings and investigated strategies used by educators and clinical instructors to address student incivility. A convenience sample of educators and clinical instructors participated by completing an electronic survey, revealing challenges such as attendance issues, lack of motivation, electronic device misuse, and skill deficiencies. The results underscored the need for comprehensive training in managing student misconduct, considering the absence of widespread faculty development in this area. Future research should explore the dynamics between administrative support and faculty reporting of misconduct and innovative approaches to faculty development. These insights contribute to enhancing educational practices and fostering professionalism in imaging sciences programs.